2008
DOI: 10.5089/9781451871050.001
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Elasticity of Residential Housing Prices

Abstract: This Working Paper should not be reported as representing the views of the IMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
2
26
0
5
Order By: Relevance
“…This consists with literature. Iossifov, Cihák, & Shanghavi (2008) summarized, for example, the international findings of such elasticity ranging from zero to around negative Table 7. Cointegration derived from VeC (1) output (dependent variable = ln P t ).…”
Section: Long-run Equilibrium In the Systemmentioning
confidence: 99%
“…This consists with literature. Iossifov, Cihák, & Shanghavi (2008) summarized, for example, the international findings of such elasticity ranging from zero to around negative Table 7. Cointegration derived from VeC (1) output (dependent variable = ln P t ).…”
Section: Long-run Equilibrium In the Systemmentioning
confidence: 99%
“…In general, there are three types of risk preferences; riskloving, risk-neutral and risk-averse. Iossifov et al (2008) indicated that investors often misunderstand the positive relationship between risk and return. Undertaking a riskier investment does not guarantee a higher return.…”
Section: Risks Of Investmentmentioning
confidence: 99%
“…The "principal-agent" framework describes a situation in which lenders cannot obtain the information that they would know about borrowers without facing a cost. 11 Iossifov, Čihák, and Shanghavi (2008) study the interest rate elasticity of residential housing prices. They point out that the acquisition of real estate assets is undertaken by means of external finance since the price of this asset is a multiple of home buyers' disposable income.…”
mentioning
confidence: 99%